A Novel Device-Integrated Drug Delivery System for Local Inhibition of Urinary Tract Infection - Stærk, Kristian; Grønnemose, Rasmus Birkholm; Palarasah, Yaseelan; Kolmos, Hans Jørn; Lund, Lars; Alm, Martin; Thomsen, Peter; Andersen, Thomas Emil (Frontiers in Microbiology, 2021)
Background: Catheter-associated urinary tract infection (CAUTI) is a frequent community-acquired infection and the most common nosocomial infection. Here, we developed a novel antimicrobial catheter concept that utilizes a silicone-based interpenetrating polymer network (IPN) as balloon material to facilitate a topical slow-release prophylaxis of antibacterial agents from the balloon to the urinary bladder. Methods: Balloon material was achieved by modifying low shore hardness silicone tubes with a hydrogel interpenetrating polymer in supercritical CO2 using the sequential method. Release properties and antibacterial efficiency of the IPN balloon treatment concept was investigated in vitro and in a porcine CAUTI model developed for the study. In the latter, Bactiguard® Infection Protection (BIP) Foley catheters were also assessed to enable benchmark with the traditional antimicrobial coating principle. Results: Uropathogenic E. coli was undetectable in urinary bladders and on retrieved catheters in the IPN treatment group as compared to control that reveal significant bacteriuria (>105 CFU/mL) as well as catheter-associated biofilm. The BIP catheters fails to prevent E. coli colonization of the bladder, but significantly reduce catheter biofilm formation compared to control. Conclusions: The IPN-catheter concept provides a novel, promising delivery route for local treatment in the urinary tract.